Clinical use and applications of histone deacetylase inhibitors in multiple myeloma - Tandon N (Dove Medical Press, 2016)
Nidhi Tandon, Vijay Ramakrishnan, Shaji K Kumar Division of Hematology, Mayo Clinic, Rochester, MN, USA Abstract: The incorporation of various novel therapies has resulted in a significant survival benefit in newly diagnosed and relapsed patients with multiple myeloma (MM) over the past decade. Despite these advances, resistance to therapy leads to eventual relapse and fatal outcomes in the vast majority of patients. Hence, there is an unmet need for new safe and efficacious therapies for continued improvement in outcomes. Given the role of epigenetic aberrations in the pathogenesis and progression of MM and the success of histone deacetylase inhibitors (HDACi) in other malignancies, many HDACi have been tried in MM. Various preclinical studies helped us to understand the antimyeloma activity of different HDACi in MM as a single agent or in combination with conventional, novel, and immune therapies. The early clinical trials of HDACi depicted only modest single-agent activity, but recent studies have revealed encouraging clinical response rates in combination with other antimyeloma agents, especially proteasome inhibitors. This led to the approval of the combination of panobinostat and bortezomib for the treatment of relapsed/refractory MM patients with two prior lines of treatment by the US Food and Drug Administration. However, it remains yet to be defined how we can incorporate HDACi in the current therapeutic paradigms for MM that will help to achieve longer disease control and significant survival benefits. In addition, isoform-selective and/or class-selective HDAC inhibition to reduce unfavorable side effects needs further evaluation. Keywords: HDAC inhibitors, Panobinostat, epigenetics, myeloma, relapse